Trainer's readiness to develop employability skills through community service courses - Abdul Latib, Azlan (2015)
This study was aimed in identifying the teaching approaches, teaching methods and assessment methods used by trainers in developing Employability skills through community service courses in three research universities in Malaysia namely Universiti Sains Malaysia, Universiti Kebangsaan Malaysia and Universiti Teknologi Malaysia. A qualitative research design was used in conducting the research. Statistical analysis technique was utilized in checking the data and calculating the frequency of a concept in the aspect to be identified. This method is also known as "Enumeration" or quantifying qualitative data. A structured interview protocol served as the instrument for data collection to identify the dominant teaching approaches, teaching methods and assessment methods used in the community service program. The results showed that the dominant teaching approach used to develop the Employability skills in the community service course is problem-based learning (PBL) approach. In addition, the findings show demonstration, lecture and quiz as among the most dominant teaching method practiced by instructor and the most dominant assessment method practiced by all respondents are examination, projects and presentation. The discussion was based on the findings and several recommendations were made to improve the quality of education, particularly at higher education level